Spojrzenie wstecz. O dwóch wątkach prozy Marka Hłaski - Kopeć, Zbigniew (Załącznik Kulturoznawczy, 2024)
Marek Hłasko’s prose won readers’ acclaim around the Polish October of 1956, and the writer himself became an important figure in literary world. The author considers to what extent Marek Hłasko’s work, the background of which was socialist realism, was considered attractive at that time because of the specific nature of the moment in which it was written, and to what extent it followed conventions that had been present in literature for a long time and dealt with important and well-established themes. Firstly, the author focuses on the similarities between the prose by Marek Hłasko and the prose by Ernest Hemingway, as indicated by critics (manner of narration, type of protagonist), and the legend accompanying both authors. Secondly, he takes The Graveyard (and the discussion it provoked) as a starting point, showing the problem of homelessness of an individual and of the whole society present in Hłasko’s prose. During the “Thaw”, this problem appeared in the prose of Marek Hłasko and in films included in the so-called “black series” of Polish documentaries. The proletarian prose of the interwar period, e.g. by Janina Brzostowska, Henryk Drzewiecki, Jan Dąbrowski, as well as in later works, e.g. by Tadeusz Konwicki or Janusz Głowacki, originates from the same sources that gave birth to Żeromski’s prose – social commitment, sensitivity and lack of acceptance for unjust forms of social life.